International Human Rights Politics & Law. A Syllabus. Revised - Henkin, Louis; Columbia Univ., New York, NY. Center for the Study of Human Rights ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Designed for first year graduate students in political science, international relations, and law, this course focuses on the contemporary concern with human rights in its international political context. The course is intended to be taught in 14 two-hour sessions; it can also be broken down into single-hour sessions. There are four major parts to the syllabus. Part 1 explores the roots and modern history of the idea of individual rights. In part 2, human rights are considered as the objective of the "International Human Rights" movement born in 1945. Part 3 addresses the problem of trying to realize human rights in an international political system made up of sovereign states whose policies reflect their national interest. Part 4 deals with human rights and foreign policy. Students are expected to read journal articles and selections from books and participate in classroom discussions. Provided for each session is a brief description of the course content, an outline of major points to be covered, discussion topics or questions, and a bibliography of readings. (RM)
Availability: Center for the Study of Human Rights, Columbia University, 704 International Affairs Building, New York, NY 10027 ($5.00).
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Civil Liberties; Foreign Policy; Graduate Study; Higher Education; History; International Relations; Justice; Legal Education; Political Science; Units of Study; Guides, Classroom -- Teacher